2020
DOI: 10.1158/0008-5472.can-19-2235
|View full text |Cite
|
Sign up to set email alerts
|

IL33 Is a Key Driver of Treatment Resistance of Cancer

Abstract: Recurrence and treatment resistance are major causes of cancer-associated death. There has been a growing interest in better understanding epithelial-mesenchymal transition, stemness of cancer cells, and exhaustion and dysfunction of the immune system for which numerous genomic, proteomic, microenvironmental, and immunologic mechanisms have been demonstrated. However, practical treatments for such patients have not yet been established. Here we identified IL33 as a key driver of polyploidy, followed by rapid p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…It was shown in a preclinical study that IL33 may directly act on tumour cells, inducing poly ploidy and rapid proliferation, and causing therapy resis tance. Use of a specific IL33blocking antibody could restore the efficacy of antiPD1 therapy in an otherwise ICIresistant subclone of the B16F10 melanoma model 179 .…”
Section: Interleukin-33mentioning
confidence: 99%
“…It was shown in a preclinical study that IL33 may directly act on tumour cells, inducing poly ploidy and rapid proliferation, and causing therapy resis tance. Use of a specific IL33blocking antibody could restore the efficacy of antiPD1 therapy in an otherwise ICIresistant subclone of the B16F10 melanoma model 179 .…”
Section: Interleukin-33mentioning
confidence: 99%
“…IL-33 treatment also drove the induction and cytotoxic activities of DC-induced Tc9 cells, a subset of effector CD8 + T cells producing cytotoxic IL-9, and further promoted the therapeutic efficacy of DC-based tumor vaccines [208]. Apart from triggering the IL-33/ST2 signaling to augment cancer immunotherapy, a number of studies showed the blockade of IL-33, ST2, or both resulted in growth inhibition of tumors [120,209,210] in association with reduced accumulation of ST2 + tumor-promoting cells, such as T reg , TAM, and IL17RB + ILC2. Furthermore, combination with ICB revealed a synergistic antitumor effect [210].…”
Section: Targeting Il-33/st2 To Augment Cancer Immunotherapymentioning
confidence: 99%
“…These cells produce AREG and IL-13, respectively, and therefore forms a protumorigenic microenvironment in the breast, lung, head and neck, and colon. 94,[97][98][99] Taken together, targeting IL-33 remains a therapeutic option for dysfunction and allergic disease. In fact, Clinicaltrials.gov has listed anti-IL-33 clinical trials in patients with asthma, food allergy, chronic rhinosinusitis and chronic obstructive airway disease (accessed 19 February 2020).…”
Section: Autoimmunological Inflammation Diseasementioning
confidence: 99%